Real-World Adherence to Multi-Target Stool DNA Testing for Colorectal Cancer Among Asian Americans - Mallik Greene PhD, DBA; Mark Camardo MS; Quang A. Le PharmD, PhD; Raja Kakuturu PhD; A. Burak Ozbay PhD, MBA; A. Mark Fendrick MD; Michael Dore MD; Paul Limburg MD (Cancer Control)
Introduction: Asian Americans have lower colorectal cancer (CRC) screening rates compared to other racial/ethnic groups. Given the importance of early detection and subsequent treatment in improving survival, this study examines adherence to first-time multitarget stool DNA (mt-sDNA) testing among Asian American patients. Methods: This retrospective study linked two data sources: Komodo Research Data + MapEnhance Komodo Lab database and the Exact Sciences Laboratories database. Asian American’s 45 years and older who were first-time users of mt-sDNA testing between 2017 and 2023, with continuous insurance enrollment for two years, were included. Adherence to mt-sDNA testing was analyzed using descriptive statistics and logistic regression to identify factors associated with adherence. Results: The final sample included 336 288 Asian American patients, primarily covered by commercial insurance (70.3%), aged 50-75 years (80.7%), female (56.5%), living in metropolitan areas (95.4%), and under the care of a primary care physician (74.9%). Overall adherence to mt-sDNA testing was 70.9%, with significant variation by payer type ranging from 60.7% for Medicaid to 72.2% for Medicare ( P < 0.0001). Overall adherence rates were approximately 70% across all age groups, sexes, and geographic regions but were notably high among gastroenterology (GI) provider patients (81.6%) and those receiving full digital outreach (via both SMS and email) (72.8%). Logistic regression identified several significant predictors of adherence: older age, males, coverage by commercial insurance, residing outside metropolitan areas, seeing GI providers, receiving digital outreach via SMS or both SMS and email, and preferring English. Conclusion: This study found that Asian American patients that were first-time users of mt-sDNA testing had high adherence rates. However, significant disparities existed within this population based on payer type and sociodemographic factors. Targeted outreach strategies are essential to reduce barriers and improve CRC screening uptake, ultimately reducing the burden of CRC in the Asian American population.